Development of Drebar Application - Mokhsin @ Misron, Mudiana; Mohd Nasdi, Nur Asyikin; Surani, Muhammad Asyraf; Ahmad Tamizi, Aimi Suhaili; Hasrul Nazre, Nur Natasha (Multidisciplinary Applied Research and Innovation, 2022)
The effective public transport is required to support economic sectors. The Drebar is a new technology smartphone application that can be used at anytime and anywhere you want. The primary application function is to provide car services for people who do not have transportation to work or other destinations as well as to assist those in need and accept any emergency. Secondly, the application is about the user, who can select both their own driver and the driver. This was specifically developed because of the numerous cases of customers being harassed by drivers that occur nowadays. Also, problems arise when women’s safety is no longer prioritized and there are no job opportunities for women in the e-hailing industry. The idea of developing an application that allows users or drivers to select their own customers based on ratings or positive reviews. This can improve customer safety while using this application. The method that thas been used through this study is how public transport works in Malaysia. Based on the existing e-hailing application, the need to upgrade new features in the application since our application is priorities more to women. The development of e-hailing services that prioritize women seeking a job in e-hailing services or seeking a female driver to make them feel safe. To maintain privacy while providing services, the application can save information on both passengers and drivers. Finally, this application is expected to increase the use of the e-hailing industry as consumers will also use public transportation to get to their destinations.